The Role of Teachers in Shaping Early Childhood Responsibility Independence in RA Al-Falah Klender - Fyryaalus Shoobihah; Andrie Chaerul; Ahmad Syahid (CV. Rayyan Dwi Bharata, 2022)
The objectives of this study are: (1) To find out data on the role of teachers in shaping the independence of early childhood responsibilities in RA Al-Falah Klender. (2) To find out data on supporting and inhibiting factors in shaping the independence of early childhood responsibilities in RA Al-Falah. To answer the formulation of research problems that have been formulated, the author uses a qualitative approach with a descriptive method. This research was conducted at RA Al-Falah Klender. The subjects used in this study are: (1) Sources of information, namely one RA manager and two teachers; (2) The source of the informant is one parent of the student. Research data were obtained from observation techniques, interviews, and documentation. The stages of research involve the stages of orientation, exploration, and member check. Data analysis used using data collation techniques, data reducation, data display, and verification. The results of the study show that the purpose of the teacher's role in forming the independence of this responsibility consists of several factors, starting with the stage of the teacher committing to the parents of students to follow the rules or regulations in school, with the hope that when students graduate from RA Al-Falah Klender are expected to be able to be independent and responsible in everything. , other factors have also been carried out well by teachers, such as facilities and infrastructure, learning methods that involve a lot of student participation dominantly, such as project making, sociodrama, conversing and so on. providing appropriate teaching media and teaching methods as stimulants to increase the independence of students, as well as an assessment system that is recorded and documented by the teacher, the type of assessment is seen from the attitude of maintaining cleanliness, the attitude of being able to obey the rules of attitude to solve problems and the attitude of responsibility towards tasks. Internal factors are supporting factors in the role of this teacher, teachers have very good interests and motivations, namely teachers have a real passion in shaping the responsibility and independence of students. On the issue of external factors, teachers are supported by the completeness of facilities and infrastructure owned by RA Al-Falah Klender, as well as excellent support from all parents of students in supporting teachers in forming independence of early childhood responsibilities at RA Al-Falah Klender